2015
DOI: 10.2174/1871527314666150529145531
|View full text |Cite
|
Sign up to set email alerts
|

The Actin Cytoskeleton as a Therapeutic Target for the Prevention of Relapse to Methamphetamine Use

Abstract: A high rate of relapse is a defining characteristic of substance use disorder for which few treatments are available. Exposure to environmental cues associated with previous drug use can elicit relapse by causing the involuntary retrieval of deeply engrained associative memories that trigger a strong motivation to seek out drugs. Our lab is focused on identifying and disrupting mechanisms that support these powerful consolidated memories, with the goal of developing therapeutics. A particularly promising mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 75 publications
2
23
0
Order By: Relevance
“…Cannula placements for intra-CNS infusions can be found in Supplemental Figure S5. Together, these data suggest that Blebb's ability to immediately disrupt METH-associated memory may be unique to the BLC (Young et al 2014(Young et al , 2015(Young et al , 2016.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Cannula placements for intra-CNS infusions can be found in Supplemental Figure S5. Together, these data suggest that Blebb's ability to immediately disrupt METH-associated memory may be unique to the BLC (Young et al 2014(Young et al , 2015(Young et al , 2016.…”
mentioning
confidence: 82%
“…Moreover, when actin depolymerizing agents are delivered to Area CA1 of the hippocampus (CA1), basolateral amygdala complex (lateral and basolateral amygdala; BLC), infralimbic region of the prefrontal cortex (IL, PFC) or nucleus accumbens (NAc) around the time of learning, memory formation fails (Fischer et al 2004;Mantzur et al 2009;Rex et al 2010;Gavin et al 2012;Bi et al 2015). Recently, we reported an unexpected and unique role for F-actin dynamics in the storage of memories associated with the highly addictive stimulant, methamphetamine (METH) (Young et al 2014(Young et al , 2015. Direct actin depolymerization within the BLC produces an immediate and long-lasting disruption of METH-associated memory storage and drug seeking, along with a concomitant loss of dendritic spines, that is both independent of retrieval and selective, having no effect on memories associated with fear or food reward.…”
mentioning
confidence: 99%
“…However, mIPSC frequency is higher in naïve KO neurons than naïve WT neurons, and cocaine exposure increases mIPSC frequency in KO but not WT neurons ( Fig 5D3). Elevated mIPSC frequency 26 in Tmod2 KO could be a neurophysiological homeostatic adaptation to compensate for increased excitability of accumbens shell neurons due to modified intrinsic and excitatory synaptic properties 95 .…”
Section: Distinct Naïve and Cocaine-induced Synaptic Propertiesmentioning
confidence: 99%
“…Perturbations in actin-assembly [12][13][14][15][16] , -capping 17,18 , -disassociating 19,20 ,nucleating 21,22 and -ADP/ATP exchange 23 proteins affects synaptic and structural plasticity. Previous studies have implicated actin dysregulation in morphine 24 , cocaine 25 , methamphetamine 26 , alcohol 27 and nicotine 28,29 addiction. Generally, psychostimulant administration correlates with increases in spine numbers, spine complexity, and spine maturity [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…Actin polymerization is the process of monomeric globular actin (G-actin) growing into complex, filamentous actin (F-actin) structures (Lin et al 2005;Kramar et al 2006), and is required for memory-promoting structural plasticity. F-actin rapidly stabilizes after fear-associated (Fischer et al 2004;Mantzur et al 2009;Rehberg et al 2010;Rex et al 2010b;Gavin et al 2012), but not METH-associated learning (Young et al 2014(Young et al , 2015(Young et al , 2016Briggs et al 2017), as indicated by differential susceptibility to actin depolymerizers, such as Latrunculin A. The sustained actin dynamics that result from METH-associated learning render these memories uniquely susceptible to disruption long after the learning event.…”
mentioning
confidence: 99%